Dealing with GIS in geography curricula: comparing Portugal and Turkey - Artvinli, Eyüp (2014)
[Excerpt] From ecological restoration to congressional redistricting, from military strategies to transportation planning, from emergency service deployment to the modelling of the impacts of climate change. GIS has become an indispensable tool for a wide array of practitioners and analysts in the public and private sectors (Murphy, 2007). It is now a standard item in planners. tool kits (Drummond, FAICP, 2008). The use of GIS in education also employs constructivist pedagogies, such as learning through inquiry and problem-based learning to facilitate greater engagement (Donert, 2006a, 2006b; Rod, Larsen, Nilsen, 2010; Bednarz, 2007; Milson & Earle, 2007; Madsen & Rump, 2012; Baker, 2005; Alibrandi, 2003). Hence, the educational side of GIS is very important in order to educate future generations. GIS is also starting to be used by geography teachers. However its presence in the curricula is not yet fully effective in many countries despite research confirming that its presence in the curriculum was important for its classroom application. [...]